TANBIH SEBAGAI PEACE EDUCATION DI PESANTREN SIRNARASA, CIAMIS, JAWA BARAT - Toipah T (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
Pesantren, which are Islamic educational institutions, are often considered by some as exclusive educational institutions. In fact, pesantren are very synonymous with heterogeneous life, even pesantren do not close their doors to non-Muslim. Pesantren have a duty to provide an understanding of tolerance, both to students and the community. This article generally provides an understanding that tolerance is an attitude to be able to accept anyone and respect each other without choosing and differentiating between any religion and any country. This research is oriented towards field research conducted at the Sirnarasa Ciamis Islamic Boarding School, West Java. This research is a type of qualitative research. Therefore, this study uses participatory observation and interview techniques. The results of this study include: First, tanbih is the main door as a peace education that is used by the Pesantren Sirnarasa to instill an understanding of the values of tolerance and minority rights. Second, as a Sufism-styled pesantren, Pesantren Sirnarasa doesn’t necessarily limit its interactions with Muslims and those who are considered to be close-knit. The caregivers and students at this pesantren have extraordinary tolerance and peace-loving attitudes regardless of citizenship status, religion and belief, as well as different cultures.Keywords: Peace education, Pesantren Sirnarasa, tanbih.